Informal Reasoning Fallacy and Critical Thinking Dispositions: A Univariate Study of Demographic Characteristics among Malaysian Undergraduates - Ramasamy, Shamala (2011)
A component in the study of critical thinking which needs to be addressed is informal reasoning fallacy. It is a type of mental trickery which is able to self-deceive undergraduates and public at large. In order to practice good critical thinking, one has to detect and get rid of these fallacies. However, students have to be disposed in detecting these fallacies prior to having high critical thinking ability. The objective of this paper is to examine the influences of Malaysian undergraduates’ background characteristics on informal reasoning fallacies and critical thinking dispositions. A cross sectional survey was conducted on 189 samples of undergraduates from three different disciplines, testing them on newly developed Informal Fallacy Reasoning Test (IFRI) and California Critical Thinking Dispositions (CCTDI). A high reliability was achieved from both tests, with Cronbach alpha .802 for IFRI and .843 for CCTDI. Finding shows that there were significant differences in disciplines on the IRFI scale, whereby respondents from Humanities background performed better than the others. Age and IRFI scores had a significant correlation. However, there was no significant difference between gender, programmes, GPA and reading hours. CCTDI differed significantly on disciplines with Humanities scoring the highest compared to Technical and Science. The total score of CCTDI differed significantly with GPA. However, age, gender, programme and reading hours did not contribute to a significant difference.